Microrna Profile of Plasma Exosomes by Nanostrings in Early Onset Compared Late Onset Preeclampsia: Preliminary Study - Sumawan, Herman; Pradjatmo, Heru; Hadiati, Diah Rumekti; Mubarika, Sofia; Giantari, Ifrinda (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Research on miRNA biomarkers in preeclampsia as part of screening, diagnosis, and prognosis has been widely conducted, but the results show contradictory results and vary based on the type of preeclampsia. This study aims to compare the profile of plasma exosome miRNA in early onset compared late onset as a preliminary study to identify the miRNA profile of preeclampsia patients in Indonesia. The study was conducted at Margono Hospital,Indonesia using plasma exosomes samples of three patients with early-onset preeclampsia and three patients with late-onset preeclampsia and processed with NanoStrings. KEGG was used to identify preeclampsia pathophysiological pathways by bioinformatic analysis of DIANA-miRPath v3.0 and microT-CDS v5.0. The results showed that the characteristics of parity, hemoglobin, systolic and diastolic blood pressure, proteinuria and BMI did not differ between EOPE and LOPE. Significantly different variables were the age of the EOPE (28 ± 5.29) vs LOPE (38.67 ± 2.06 mmHg), pregnancy weight gain (10.0 vs 15.33), and fetal weight in EOPE (1550 ± 132 g) vs LOPE (2693 ± 716 g). The results showed that the 24 miRNAs differed significantly. The three highest expression miRNAs in the EOPE group were miR-196b-5p, miR-190a-5p, and miR-515-3p. In contrast, the three lowest expression miRNAs are miR-3179, miR-181a-5p, and miR-15b-5p. Pathway analysis of the upregulated miRNA involved the ErbB signalling pathway, Proteoglycan in cancer, and Lysin degradation. Downregulated miRNA targets involved in the HIPPO signalling pathway, fatty acid biosynthesis, and TGF-β signalling pathway. Conclusions: The preliminary study results indicated significant differences in miRNA expression, suggesting that EOPE is influenced by aggressive cellular signaling and metabolic dysregulation, while LOPE is more linked to the disruption of growth-inhibiting pathways and fatty acid metabolism. These unique miRNAs establish a robust foundation for subsequent validation studies utilizing bigger samples as a prospective biomarker panel.